Intrinsic limitations of nanofiltration membranes to achieve precise selectivity in water-based separations - Epsztein, Razi (Frontiers in Membrane Science and Technology, 2022)
Nanofiltration (NF) membranes have been used for solute-solute separations for many years with recent interest targeting more challenging separations that require precise selectivity between solutes. In this perspective article, we aim to challenge (but not disprove) the prevalent notion that NF membranes are suitable for precise separations. We first provide and analyze selectivity data from the literature of three important separations including monovalent-divalent ion selectivity, separations involving organic molecules, and the more ambitious separations of ions with the same charge. We then introduce the terms rejection-based selectivity and transport-based selectivity to distinguish between the commonly “rough” separations pursued in NF (e.g., water softening) and the more visionary separations required for precise selectivity (e.g., transport of lithium through specific recognition sites), respectively. Using these terms, we discuss two major intrinsic limitations to achieve precise selectivity in NF systems; namely, the need for a solute-specific membrane that can transport additional species (i.e., water, and in the case of a salt – the complementary ion) and the detrimental effect of concentration polarization. We conclude with guidelines and principles to overcome these limitations.